The contribution of Jalal al-ddin cabd al-rahmanal-suyuti (d: 1445 ad) in the works of sharh Al-hadith: Analysis of six works in Sunan Al-sittah - Abdullah W.H.; Zarif M.M.M. (Innovare Academics Sciences Pvt. Ltd, 2024)
Indexed by Scopus